PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA KONSEP DUALISME GELOMBANG PARTIKEL - Yusron Darojat; Eko Suyanto; Wayan Suana (Jurnal Pembelajaran Fisika, 2015)
This research aimed to produce interactive learning media based on Information and Communication Technology (ICT) that are effective to learn particle waves dualism concept for students and aimed to identify students response about the attractiveness of the product. This research used research and development (RD) method with implementation procedure referenced on the research procedure according to Suyanto and Sartinem that were consisted of seven steps, that is: (1) analysis of the needs; (2) identification of resources; (3) identification of product specifications; (4) product development; (5) internal test; (6) external test; and (7) production. This research produced interactive learning media in the concept of particle waves dualism as a source of independent learning for students grade XII IPA SMA Islam Terpadu Baitul Muslim Way Jepara. The media was declared effective based on the success of students reached the minimum completeness criteria (is called KKM) and it was declared attractive based on questionnaire analysis results.Penelitian ini bertujuan menghasilkan media pembelajaran interaktif berbasis Teknologi Informasi dan Komunikasi (TIK) yang efektif dalam membelajarkan konsep dualisme gelombang partikel pada siswa serta untuk mengetahui tanggapan siswa terhadap kemenarikan dari produk yang dihasilkan. Penelitian ini menggunakan metode research and development (RD) dengan prosedurpelaksanaan mengacu pada prosedur penelitian menurut Suyanto dan Sartinem yang terdiri dari tujuh langkah, yaitu: (1) analisis kebutuhan;(2) identifikasi sumberdaya;(3) identifikasi spesifikasi produk; (4) pengembangan produk;(5) uji internal; (6) uji eksternal;dan(7) produksi. Penelitian ini menghasilkan media pembelajaran interaktif pada konsep dualisme gelombang partikel sebagai sumber belajar mandiri bagi siswa kelas XII IPA SMA Islam Terpadu Baitul Muslim Way Jepara. Media yang dihasilkan dinyatakan efektif berdasarkan keberhasilan siswa mencapai Kriteria Ketuntasan Minimal (KKM) dan dinyatakan menarik berdasarkan hasil analisis angket.Kata kunci: dualisme gelombang partikel, media pembelajaran interaktif, penelitian pengembangan